Analisis Pengaruh Viskositas Oli dan Beban Kejut terhadap Karakteristik Kompresi Shock Absorber Teleskopik Sepeda Motor - Hisyam Syaifulloh; Khambali Khambali; Santoso Santoso; Eko Yudiyanto (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effect of the combination of oil viscosity and shock load on the compression characteristics of telescopic shock absorbers on motorcycles, which include depth, time, and compression speed parameters. The experiment was carried out using two levels of oil viscosity, namely 10 cSt and 15 cSt (equivalent to SAE 10W and SAE 15W), as well as two shock load variations, namely 40 kg and 50 kg, which were dropped vertically from a height of 30 cm. Compression depth measurements were carried out using a slow-motion camera at a speed of 240 fps and the results were validated using Kinovea software. Meanwhile, the compression time measurement is carried out with a stopwatch, and the compression speed is calculated from the results of the comparison between the compression depth and the compression time. The experimental data were analyzed using Minitab software with the Two-Way ANOVA method to determine the influence of each variable on response. The results of the analysis showed that oil viscosity and shock load had a significant influence on the compression depth, while the viscosity of the oil also significantly affected the compression speed. However, neither the viscosity of the oil nor the shock load exerted a significant influence on the compression time. To support the results of the experiment, a mass-spring-damper system theory model approach was used, which represents the dynamic behavior of shock absorbers. This model helps to explain the compression response to changes in fluid and load parameters theoretically. Based on the analysis of experimental results and model simulations, the optimal combination that provides the best performance is found in the use of oil viscosity of 10 cSt (SAE 10W) with a shock load of 50 kg.